Puberty in South American Bos indicus (Zebu) cattle - Nogueira, G. P. (Elsevier B.V., 2004)
Puberty in Zebu heifers follows a pattern characterized by a decrease in the steroid feedback mechanism and an increase in LH concentration, which result in the first ovulation followed by a short estrous cycle and the onset of normal cycles thereafter. These events are similar to those observed in Bos taurus cattle but occur at a later age. The late onset of puberty is both genetic and environmental in origin and is reflected by the age at first calving that can be at 40 months of age or older in these animals. Age at puberty in Zebu heifers has been shown to have a high heritability. Consequently, selecting precocious heifers may be an effective means of reducing age at puberty in these animals and this approach is being adopted in commercial practice. Genetic selection is not the sole solution to the problem because environmental improvements are necessary, particularly in terms of improved nutrition. South American Zebu cattle are usually subject to sub-optimum nutritional and management conditions and, hence, exhibit late onset of puberty. Hybrids of Zebu and Bos taurus cattle exhibit heterosis in respect of the age of puberty with earlier onset than expected in crossbred animals. Recently, purebred South American Zebu cattle have been shown to have Bos taurus genes, indicating that there have been previous attempts to improve their productivity using this approach. It was concluded that the age at first calving in South American Zebu cattle can be reduced by exposing well-fed, yearling heifers to bulls and selecting, over several generations, those animals that become pregnant at an early age. (C) 2004 Published by Elsevier B.V.
Keywords: cattle; Bos indicus; Zebu; puberty; heifers; South America